Internationalizing the teaching of psychology - Rich, Grant Jewell; Gielen, Uwe P. 1940-; Takooshian, Harold (Emerald Publishing Limited : IAP-Information Age Publishing, Inc., 2017)
"How can psychology professors in the USA and other nations make their courses more international?" This question is addressed in this indispensable new sourcebook, co-authored by 73 contributors and editors from 21 countries. In recent decades psychology has evolved from an American-dominated discipline to a much more global discipline. Preliminary estimates by Zoma and Gielen (2015) suggest that approximately 76%-78% of the world's one million or so psychologists reside outside the U.S. However, most textbooks in the field continue to rely predominantly on research conducted in North America and Europe. Our book is intended to introduce psychology instructors to a variety of broad perspectives as well as specific suggestions that can support their efforts to internationalize their course offerings at both the undergraduate and graduate levels. In this way they can prepare their students to become more culturally sensitive and function more effectively as citizens and psychologists in the evolving globalized world. To achieve these ambitious goals the editors have assembled an international group of 73 distinguished contributors who, taken together, have taught and conducted research in all regions of the world. The chapters in the book include both core areas of psychology and subdisciplines that represent rapidly expanding and internationally important areas such as cross-cultural psychology and the psychology of gender. The chapters cover key topics and areas included in the course offerings of psychology departments both in the United States and in other countries. In addition to a discussion of international perspectives relevant to a given area, all chapters include an annotated bibliography of pertinent books, articles, web-related materials, films, videos, and so on. Based on this information, both highly experienced and less experienced psychology instructors can add globally and culturally oriented dimensions to their respective courses. This is important because universities, departments, and accrediting agencies increasingly put pressure on instructors to broaden and internationalize their courses.
Keywords: Psychology -- Study and teaching.; Psychology -- General.; Psychology.; elektronické knihy; electronic books